Sustainable development for public administration - Kokab, Adila (Oakville, Canada Society Publishing, 2018)
Examines the sustainability agenda of development as it applies to the principles and practices of public administration. The book also looks at the definitions and theories of sustainable development and public administration, and the application of sustainable development to public administration.
Chapter 1 Core concepts of sustainable development and public administration -- Chapter 2 Principles of sustainable development -- Chapter 3 Introduction to public administration theory and practice -- Chapter 4 Critical Issues in the sustainability agenda -- The importance of people and Communities -- Chapter 6 A consultative and participatory framework -- Chapter 7 The reform and modernization Agenda -- Chapter 8 Building and using capacity -- Chapter 9 Oversight and follow-up framework -- Chapter 10 Multidisciplinary and interdisciplinary sustainable development work -- Chapter 11 Linking the local to the global -- Chapter 12 Sustainable development for Public Administration -- Prologue -- Appendices -- References -- Index
Includes bibliographical references and index
Keywords: Sustainable development -- Political aspects; Public administration -- Environmental aspects